Essays in exchange rate economics - Wali, Muammer Reza Bin (Curtin University, 2014)
This research analyses the key issues in exchange rate economics. It provides a systematic treatment of exchange rate volatility and its manifestations, the presence of nonlinearity in exchange rates, and the interaction between national price levels and exchange rates. The approach is empirical. The results of this study are expected to contribute to an understanding of the existing empirical puzzles that profoundly impact economic policy-making and business.